Explicando o perfil do mediador de conflitos a partir da personalidade e dos valores humanos - Guimarães, Clara Lohana Cardoso (2019)
This dissertation aims to explain the mediator 's profile based on personality traits mediated by human values. To achieve this goal, three studies were carried out. Study 1 aimed at elaborating the Conflict Mediator’s Profile Scale (EPMC), gathering preliminary evidence of its validity and accuracy. 248 university students, from the health area, human and exact, with a mean age of 26 years (SD = 7.66), 76.2% women, from a public university (72.6%) participated. They answered EPM and a sociodemographic questionnaire. The results of the exploratory factorial analysis, using the HULL, MAP and AP criteria, suggested unidimensionality of the instrument, which presented evidence of favorable validity and precision (Cronbach's α and McDonald's omega = 0.90); Study 2, with the purpose of testing the structure found in Study 1, counted on 240 university students, distributed equally among the courses of Law and Psychology. The mean age was 27 years (SD = 7.70), 52.1% women and private university (81.3%). The results showed acceptable psychometric parameters [X² / gl = 2.07, CFI = 0.92, TLI = 0.91 and RMSEA = 0.07 (IC 90% = 0.053 - 0.081), with Cronbach's α and composite reliability similar (0.89); and Study 3 aimed to identify the relationship between the personality traits, the valued subfunctions and the mediator profile, to verify the contribution of the personality traits, the value subfunctions and the sociodemographic variables (graduation course, age, sex and type of institution ) in the explanation of the mediator profile, and, finally, to test the explanatory model of the mediator profile. A total of 285 university students enrolled in the Law and Psychology courses, comprised of the last three periods, with a mean age of 27.32 years (SD = 7.80), 59.3% women, and a private university (80.7%). responded to the instruments of Study 1, plus the Five Major Factors Inventory and the Core Values Questionnaire. Pearson's correlations demonstrated a positive and statistically significant (p <0.05) relationship of the mediator profile with the traits kindness (r = 0.35), openness to experience (r = 0.33), conscientiousness (r = 0.32 ) and extroversion (r = 0.21), in addition to suprapersonal (r = 0.27) and interactive sub-functions (r = 0.24). Subsequently, a hierarchical multiple regression was performed, with a statistically significant model in the final step [F (7; 644) = 18.28; p <0.001, R² = 0.24), entering as predictor variables of the mediator profile the course, with the highest scores of those who study Psychology (β = 0.14, p = 0.01), the personality traits (conscientiousness , β = 0.21, p <0.001, openness to experience, β = 0.20, p <0.001, and amiability, β = 0.18, p = 0.002) and the interactive subfunction (β = 0.12; p = 0.03). From this, a mediating model was tested considering the mediator profile as a criterion 15 variable, personality traits as independent variables and the interactive subfunction as mediator, whose results showed that the traits conscientiousness and openness to the experience explain the profile of the mediator of form directly, independent of the value subfunction. However, mediated by the interactive subfunction, only amiability showed significant results. Thus, it is believed that personality traits and human values are important variables in explaining the formation of this profile, providing empirical data that can facilitate the recruitment of these professionals, as well as promoting training strategies and interventions for the improvement of the performance. In sum, it is hoped that the objectives have been achieved and that this work contributes to Social Psychology, especially in explaining the profile of the mediator, from a psychological perspective, since most studies about mediation are constituted in the area of Right.